2015
DOI: 10.1074/jbc.m114.602193
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Model Systems Reveal Similarities and Differences between Membrane Interaction Modes of MCL1 and BAK

Abstract: Background: BCL2 family protein interactions with and at mitochondrial membranes are poorly understood. Results: Fluorescence-based studies applied to minimalist model systems provide new insight into membrane activities of MCL1 and BAK under apoptotic-like conditions. Conclusion: Membrane interaction modes of MCL1 and BAK share particular features but also display important differences. Significance: BCL2 family protein function can be modulated at the mitochondrial membrane level through manifold mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These sites can then be entry points for BAX and BAK insertion, which agrees with the fact that CL and Ca 2+ have been shown to facilitate BAX insertion, oligomerization, and membrane permeabilization [232,[244][245][246][247][248]. CL has also been shown to promote membrane targeting of BCL-X L , as well as MCL-1 and BAK, when using small unilamellar vesicles, supraphysiological concentrations of CL or when combined with BID [249,250]. Once recruited, molecular dynamic simulations suggest that CL might also regulate the function of BCL-X L through exposure of its BH3-binding pocket [251].…”
Section: Cardiolipinsupporting
confidence: 70%
“…These sites can then be entry points for BAX and BAK insertion, which agrees with the fact that CL and Ca 2+ have been shown to facilitate BAX insertion, oligomerization, and membrane permeabilization [232,[244][245][246][247][248]. CL has also been shown to promote membrane targeting of BCL-X L , as well as MCL-1 and BAK, when using small unilamellar vesicles, supraphysiological concentrations of CL or when combined with BID [249,250]. Once recruited, molecular dynamic simulations suggest that CL might also regulate the function of BCL-X L through exposure of its BH3-binding pocket [251].…”
Section: Cardiolipinsupporting
confidence: 70%
“…Other than its role in BAX and BAK activation, the OMM also has a critical role in the interaction of active BAX and BAK with prosurvival BCL-2 proteins. 109 , 110 , 111 Known as the 'retrotranslocation' theory, it has been shown that cytosolic BAX and BAK spontaneously attach to the OMM, which promotes their homodimerization and MOMP, unless prosurvival members are present to heterodimerize with them at the OMM and cause their retrotranslocation into the cytosol. 112 , 113 Thus, it is thought that in healthy cells BAX and BAK are retained in the cytosol or continuously retrotranslocated by prosurvival proteins to avoid MOMP.…”
Section: Bcl-2 Family Effectors: How To Permeabilize the Ommmentioning
confidence: 99%
“…In the case of GSDMs, it seems that arcs are intermediates transitioning into complete rings in which lipids are excluded. However, the BAX/BAK pores are flexible and dynamic, and their size depends on protein density at the membrane and on lipid composition (Landeta et al , 2011; Bleicken et al , 2013; Landeta et al , 2015; Subburaj et al , 2015; Salvador‐Gallego et al , 2016; Cosentino & Garcia‐Saez, 2017). This, together with the difficulty to define interaction surfaces between BAX/BAK dimers, supports a model in which protein dimers and lipids could be intermixed with each other also in the ring‐like structures.…”
Section: Pore Formation In Membranes Is a Conserved Strategy To Kill mentioning
confidence: 99%